HISTORICAL DISCOURSE AND ALLUSION - Zhakulayev, Adil; Takirov, Sarzhan; Soylemez, Orhan (The Eurasian Humanities Institute, 2022)
Many studies have been conducted around the problem of allusion in the world and have not yet ceased to be relevant. The allusion is very complex, diverse, and the ways of transmission in the artistic text are different. Closely related to history. That is, it is reflected in the artistic text by indirect references to historical data. This article discusses the category of historical discourse and features of allusion and interpretation of historical facts in an artistic text. By studying the allusion, researchers pay attention to its functions, typologies and types, and specific characteristics. If we consider history and allusion in a very close relationship, it is obvious that allusion has its own place in the transmission of historical discourse in the artistic text in a work of art. In this article, the historical inscriptions in the text of M.Magauin's work «Kyрshak beauty» is relatively analyzed within the framework of scientific-historical, socio-political, artistic-historical, and cultural discourses. The influence of a historical and artistic text on historical consciousness is studied. The article is guided by the works of such scientists as N.Fateeva, A.N. Pasco, J.Weixlmann, A. G. Mamaeva, A. A. Pelttari, A. S. Adilova on the topic of discourse. Attempts are made to identify the features of the relationship between allusion and historical discourse. In the course of the study, methods of comparison, comparison-analysis, interpretation, semantic, were used.